Pemberian Static Stretching Exercise Dapat Meningkatkan Fungsional Punggung Bawah Pada Penjahit - Karunia Saraswati, Ni Luh Putu Gita; Adiputra, Luh Made Indah Sri Handari; Pramana Putra, Putu Yudi (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 5 No 2 (2019): Volume 5 No 2 Desember 2019, 2019)
Tailor is the most important asset among the textil industry resources to win the competition. Work posture when tailoring and work will generate musculaskeletal disorders such as muscle tension and pain in the lower back area. Both complaints will have an impact on the decreased functional ability of the lower back which leads to a decrease in productivity. The results of the initial interview and assessment using the Rapid Upper Limb Assessment (RULA) found the work attitudes of the tailor to be at level 6 interpreted as the work position of the tailor needs to be changed immediately. The goal of this study is to prove the static stretching exercises can improve the functional ability of the lower back area. This research method is experimental with one group pre test design post test design. The study was conducted in April 2018 with repetition 3 times a week for 4 weeks. The research sample of 15 people. Functional measurement of the lower back using a modified-modified Schoober test. Based on the results of data analysis using Paired Sample t-test indicates that there are significant changes after giving static stretching exercise (p<0.05). The conclusion of this study is that static stretching exercise can improve the functional ability of the lower back.